2007
DOI: 10.3727/000000007783465208
|View full text |Cite
|
Sign up to set email alerts
|

Subcultured Odontogenic Epithelial Cells in Combination with Dental Mesenchymal Cells Produce Enamel–Dentin-Like Complex Structures

Abstract: We showed in a previous study that odontogenic epithelial cells can be selectively cultured from the enamel organ in serum-free medium and expanded using feeder layers of 3T3-J2 cells. The subcultured odontogenic epithelial cells retain the capacity for ameloblast-related gene expression, as shown by semiquantitative RT-PCR. The purpose of the present study was to evaluate the potential of subcultured odontogenic epithelial cells to form tooth structures in cell-polymer constructs maintained in vivo. Enamel or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…DFSCs are able to form cementum and bone tissues in vitro and in vivo (Kemoun et al, 2007;Yokoi et al, 2006). Human dental epithelial stem cells (hDESCs) can be isolated from the third molar that develops late after birth (Honda et al, 2007;Honda et al, 2005). Another source of hDESCs is the epithelial root sheath that disintegrates into strands of epithelial cells, also known as epithelial rests of Malassez (ERM).…”
Section: Cells In Vitro and In Vivomentioning
confidence: 99%
“…DFSCs are able to form cementum and bone tissues in vitro and in vivo (Kemoun et al, 2007;Yokoi et al, 2006). Human dental epithelial stem cells (hDESCs) can be isolated from the third molar that develops late after birth (Honda et al, 2007;Honda et al, 2005). Another source of hDESCs is the epithelial root sheath that disintegrates into strands of epithelial cells, also known as epithelial rests of Malassez (ERM).…”
Section: Cells In Vitro and In Vivomentioning
confidence: 99%
“…It has also been shown that the presence of the BM can affect the differentiation of stem cells into odontoblasts. 53,54 In addition, the dermal papilla and dermal sheath cells induce the differentiation of keratinocytes into hair follicles. 55 Furthermore, the variation of the underlying fibroblast cells alter the phenotype of the respiratory epithelium between the proximal alveolar or distal tracheal phenotypes.…”
Section: Effect Of Heterotypic Interactions On Epithelial Cellsmentioning
confidence: 99%
“…In these studies, epithelia were removed and cells dissociated enzymatically. Precursors were then amplified and associated with MSC (originated from the same tooth) in Stem cells for tooth engineering vitro in contact with biomaterials such as collagen sponges or synthetic polymers (Honda et al, 2005(Honda et al, , 2007bYoung et al, 2002). These approaches are promising for tooth formation and/or regeneration.…”
Section: Periodontal Ligament Stem Cells (Pdlsc)mentioning
confidence: 99%